George Crumb: Profile of a Composer - Gillespie, Don; Chase, Gilbert 1906-1992 (New York Peters, 1986)
George Crumb: Portraits and Patterns, by Gilbert ChaseGeorge Crumb, by David BurgeBiography, by DavidCopeMusic: Does It Have a Future?, by George CrumbGeorge Crumb, American Composer and Visionary, by Suzanne MacLeanGeorge Crumb: Two Personal Views: No.1, Reflections on Twenty Years, by Jan DeGaetani; No.2, Recording ANCIENT VOICES OFCHILDREN, by Teresa SterneQuotes from ReviewsInterview: George Crumb / Robert ShuffettCrumb's Music:ExcerptsMAKROKOSMOS I and II: A Case Study of George Crumb's Compositional Process, by Christopher WilkinsonThe Element ofSound in NIGHT OF THE FOUR MOONS, by Stephen ChatmanGeorge Crumb: Friend and Musical Colleague, by RichardWernickPhotographsDe Oraculo Crumbi, by Eugene NarmourContributors (brief biographies)Bibliography(listings of books, magazine articles, newspaper articles, dissertations and theses, wri tings by Crumb, and interviews withCrumb)DiscographyReviews of Recordings (listings only)Selected Reviews of Performances (listingsonly)Selected Choreography to Crumb's MusicAnnotated Chronological List of Works
Keywords: Crumb, George -- 1929-2022; Composers; Biography; USA